The Politicization of the Domestic in "The Woman of Colour" - Mimi Kurlas (The Owl)
Modern people often gripe that “everything has become political.” Whether it be football players kneeling during the national anthem, mega-churches endorsing presidential candidates, or schools overhauling curriculum at the direction of governors, many people feel as though our apolitical spaces have been co-opted for one agenda or another. Underlying this frustration is the view that apolitical spaces do actually exist; that there are spaces that have nothing to do with power structures, politics, or anything of that sort. After all, the domestic, the mundane, is supposed to be familial and familiar—devoid of stark differences and inhospitable to the conflicts of the outside. Others hold the opposite view. For instance, in the wake of the election, some proposed we should look at phenomena such as the rise of the “trad wife” influencer to explain the popular vote win for Donald Trump. Before these journalists and TikTok philosophers, however, the anonymously-published 1808 novel, The Woman of Colour, offered a picture of the domestic sphere that is not totally familial and familiar, whose inhabitants brush up and chafe against each other at the site of their differences—a domestic sphere that mirrors the complicated and political outside in many ways. This portrait of the domestic sphere in The Woman of Colour as the locus of societal ill and corruption renders the domestic and other mundane aspects of life deeply political. Though it is ostensibly distant from the issues of cosmopolitan society, Anonymous posits that the domestic is the beginning and end of a culture’s story. Unsurprisingly, this text has not always been read in this way.